Dynamics of the relationship between the main stock indices in the context of changes in external factors - Sosnov, Ihor; Savchenko, Roman; Mehyar, Samer (Center for Tech and Media Research, 2024)
Economic development presupposes the sustainable functioning of all structural elements, among which due attention is given to the stock market. This market allows us to understand the dynamics of the supply/demand relationship, redistribute resources between various business entities, and act as a platform for investment. To implement such tasks, an analysis of the dynamics of quotes for the corresponding shares or their group, which make up various stock indices, is used. Based on this, the work analyzed the dynamics of quotes for the main stock indices. For these purposes, the features of each of the considered indices are considered separately. The paper also provides an assessment of the mutual dynamics for some pairs of major stock indices. This analysis is made on the basis of constructing estimates of wavelet coherence. This approach allows us to justify possible investment strategies and the timing of entry into the corresponding segment of the stock market. The results of the study are presented in the form of graphs and diagrams. This helps to understand the progress of the study and evaluate the results obtained.
Keywords: dynamics; relationship; quotes; stock market; stock indices; statistical analysis; wavelet analysis; mutual analysis